Detection of Malnutrition in Older Infants by Measurement of Mid arm Circumference - Jayashree Nadkarni; Utkarsh Sharma; Ravindra Bagde; Rashmi Dwivedi (International Journal of Medical Research and Review, 2013)
Introduction- Mid-arm circumference (MAC) has been widely used as an age-independent indicator of undernutrition at 1-5 years of age. Its role below one year of age has not been extensively studied. Growth faltering which predicts protein-energy malnutrition (PEM) usually begins between ages 6 and 12 month. This study aimed to determine the age-independent character of MAC within 7-11 month age group and search for a reliable cut off point.Methods- This institutional based, cross-sectional, observational study was done at three government hospitals including a teaching tertiary level hospital. Study variables were age, sex, height, body weight & mid arm circumference. Mid arm circumference was validated against weight for age percentage and Standard deviation score.Results- Mean MAC of the infants increased very little with age from 7-11months. The cut off points from 13.0 to 12.5 cm showed maximum diagnostic accuracy.Conclusions- MAC measurement is a simple and valid tool for detection of early PEM in this crucial age bracket However, further studies are suggested, preferably community based and in a larger sample to establish the validity of MAC to detect PEM in infants.